INSIDE DIVERGENT : THE INITIATIATE'S WORLD - Bernard, Cecilia, (KATHERINE TEGEN BOOKS, 2013)
This eye-catching volume takes you inside the film version of Divergent where you'll discover the factions, meet the initiates, and enter the thrilling dystopian world.